Effect of alliums on total cholesterol content of liver and muscle of Japanese quail (Coturnix coturnix japonica) - KUMAR, V GIRISH; SURENDRANATHAN, K P (The Indian Journal of Animal Sciences, 2014)
Effect of onion, garlic, age and sex on total cholesterol in liver and muscle of quails was studied. No significant effect of onion or garlic on the total cholesterol content of liver and muscle was observed. This effect was not significant even when the birds were fed for 3 and 6 weeks duration. However, the results on the basis of pooled data obtained as per statistical analysis revealed a significant decrease in the total cholesterol content in liver and muscle. The total cholesterol contents in the liver and muscle in both sexes at 3 physiological stages of growth, viz. 3-week old (immature), 6-week old (onset of sexual maturity) and 9-week old (mature) birds were determined. Inconsistent results were obtained when observed between age within a sex or between sex within an age group.